2017
DOI: 10.1007/s00167-017-4510-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined anterior cruciate ligament reconstruction and lateral extra-articular tenodesis does not result in an increased rate of osteoarthritis: a systematic review and best evidence synthesis

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 50 publications
(107 reference statements)
6
87
1
2
Order By: Relevance
“…The clinical importance of over constraint of internal rotation is currently unknown, but to date there is no known evidence supporting lateral extra-articular procedures causing or accelerating the development of osteoarthritis [11]. Whilst remaining popular in Europe, the addition of an LET fell out of favour in North America following publications from O'Brien et al [40] and Anderson et al [2].…”
Section: Biomechanics Of Lateralmentioning
confidence: 99%
“…The clinical importance of over constraint of internal rotation is currently unknown, but to date there is no known evidence supporting lateral extra-articular procedures causing or accelerating the development of osteoarthritis [11]. Whilst remaining popular in Europe, the addition of an LET fell out of favour in North America following publications from O'Brien et al [40] and Anderson et al [2].…”
Section: Biomechanics Of Lateralmentioning
confidence: 99%
“…26 A 2017 systematic review focused specifically on the occurrence of secondary osteoarthritis following lateral extra-articular tenodesis (LEAT). 7 After analyzing 8 studies with 5-to 10-year follow-up or greater, the authors concluded that ''the best available evidence would suggest that the addition of a LEAT to ACLR does not result in an [increased] rate of osteoarthritis in the knee.'' 7(p1149) As with any study, the results of the STABILITY trial are most pertinent to the participants and methods involved in the investigation, a point the authors emphasize in their discussion.…”
mentioning
confidence: 99%
“…Long-term considerations include potential overconstraint and the subsequent development of degenerative arthritis. Although there are limited data, Devitt et al 16 reported in a best-evidence study that no increased rate of osteoarthritis developed 11 years after isolated LET and primary ACLR augmented with a LET procedure. 16 Our experience with this technique has shown promising results thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are limited data, Devitt et al 16 reported in a best-evidence study that no increased rate of osteoarthritis developed 11 years after isolated LET and primary ACLR augmented with a LET procedure. 16 Our experience with this technique has shown promising results thus far. To date, 51 patients younger than 20 years of age have undergone the modified Lemaire procedure alongside ACLR with quadriceps tendon autograft.…”
Section: Discussionmentioning
confidence: 99%